2003
DOI: 10.1007/s00421-002-0734-x
|View full text |Cite
|
Sign up to set email alerts
|

Austrian Moderate Altitude Study (AMAS 2000) – fluid shifts, erythropoiesis, and angiogenesis in patients with metabolic syndrome at moderate altitude (≅1700 m)

Abstract: It was hypothesized that subjects with metabolic syndrome (hypertension, obesity, hyperlipidemia, diabetes mellitus): (1) develop measurable peripheral edema at moderate altitude and (2) might show differences on erythropoiesis, iron status and vascular endothelial growth factor (VEGF) in comparison to healthy subjects during and after a long-term stay (3-week exposure) at moderate altitude (congruent with 1700 m). Twenty-two male subjects with metabolic syndrome were selected. Baseline investigations (t1) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 43 publications
0
20
1
Order By: Relevance
“…The favorable effects of a sojourn at moderate altitude on cardiovascular parameters and on fat and glucose metabolism have already been demonstrated in the pilot project of AMAS-2000 [20,21]. Patients participating in our AMASsubstudy exhibited also improvements in cardiovascular parameters (reduction in resting heart rate, systolic and diastolic blood pressure), and borderline (LDL-C, HDL-C) or significant changes (total cholesterol, triglycerides) in metabolic parameters.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The favorable effects of a sojourn at moderate altitude on cardiovascular parameters and on fat and glucose metabolism have already been demonstrated in the pilot project of AMAS-2000 [20,21]. Patients participating in our AMASsubstudy exhibited also improvements in cardiovascular parameters (reduction in resting heart rate, systolic and diastolic blood pressure), and borderline (LDL-C, HDL-C) or significant changes (total cholesterol, triglycerides) in metabolic parameters.…”
Section: Discussionmentioning
confidence: 67%
“…The main goal of AMAS-2000 was to investigate the effects of a 3-week exercising sojourn at moderate altitude (1700 m) on cardiovascular, metabolic and hematological parameters on tourists with metabolic syndrome. Initial results from the pilot study demonstrated short-term favorable effects on fat and glucose metabolism and a reduction in blood pressure [20,21].…”
Section: Introductionmentioning
confidence: 97%
“…Previous publications of data derived from the AMAS study reported favorable effects to a 3-week exposure to 1700 m on body mass, blood pressure, heart rate, Insulin resistance and glucose tolerance (11,12). Among the mediators chosen for the present study to represent an activated immune system in patients with metabolic Syndrome, only neopterin and sTNF-R75 showed a slight but transient increase on days 4 and/or 9 at moderate altitude as compared to baseline levels.…”
Section: Discussionmentioning
confidence: 77%
“…Endothelial dysfunction and increased levels of endothelin-1 are also associated with atherosclerosis, oxidative stress, inflammation, the metabolic syndrome, and malnutrition (12)(13)(14). There are indications that inflammation interact with erythropoiesis, resulting in reduced erythropoietin and red blood cell counts (14,15).…”
Section: Introductionmentioning
confidence: 98%